The determinant factors that affect the price of housing in Malaysia / Mohamad Azman Mohd Arif - Mohd Ariff, Mohamad Azman (Faculty of Business Management, 2014)
The main purpose of this study is to measure the relationship between macroeconomic variables and the housing price. This paper examines empirically whether the increasing trend in the Malaysian housing price is related to changes in the interest rate, consumer price index and stock price KLCI. The empirical data were collected from data stream using monthly basis from 2003 to 2013. The paper provides empirical results that the interest rate, consumer price index and stock price KLCI are the key determinants of housing prices. The general finding of this paper strongly suggests that housing bubbles in the Malaysian residential property market are becoming bigger and stronger. The paper is useful for researcher, investors (buyer), and organization to know which factors to account for in housing investment decision. This paper can serve as a guide for the government in stabilizing the residential housing price in Malaysia.